2015
DOI: 10.1007/s00703-015-0377-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model ensemble forecasts of tropical cyclones in 2010 and 2011 based on the Kalman Filter method

Abstract: This study conducted 24- to 72-h multi-model ensemble forecasts to explore the tracks and intensities (central mean sea level pressure) of tropical cyclones (TCs). Forecast data for the northwestern Pacific basin in 2010 and 2011 were selected from the China Meteorological Administration, European Centre for Medium-Range Weather Forecasts (ECMWF), Japan Meteorological Agency, and National Centers for Environmental Prediction datasets of the Observing System Research and Predictability Experiment Interactive Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The consistency of these findings across multiple studies highlights the importance of the SQM technique in climate modeling [ 21 , 48 , 49 , 70 ]. Many studies have shown that the MME forecast performance is superior to the forecast of an individual (one-model-based) ensemble prediction systems [ [71] , [72] , [73] , [74] , [75] ]. The findings suggest that MME approach can provide more accurate and robust climate projections, which can inform long-term adaptation planning and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency of these findings across multiple studies highlights the importance of the SQM technique in climate modeling [ 21 , 48 , 49 , 70 ]. Many studies have shown that the MME forecast performance is superior to the forecast of an individual (one-model-based) ensemble prediction systems [ [71] , [72] , [73] , [74] , [75] ]. The findings suggest that MME approach can provide more accurate and robust climate projections, which can inform long-term adaptation planning and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the examined MME method is one of the most basic and straightforward multimodel ensemble methods, which assigns all models with the same role. Considering the deficiency of MME in reducing the BIAS and DIST of wind forecasts, the multimodel ensemble methods based on more complex algorithms assigning different weights for different models, including Kalman filter [52,53], object-based diagnosis [54] and deep learning methods [6,55], are also on the way to be utilized to further improve wind forecast ability. Furthermore, with the development of modern observation channels and technologies, observations are enriched and could be taken into consideration to assess and calibrate the model products in a more realistic way.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Somehow, linear regression is a crude method while canonical correlation analysis and stepwise pattern projection methods are considered an advanced one for downscaling. Furthermore, other sophisticated methods like statistical-dynamical Kalman Filter method [42], hyperensemble method [43], and Artificial Neural Network method can be used for multimodel ensemble prediction of rainfall in our next study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%